إزالة الإعتراض عن محقي آل إباض - أطفيش, محمد بن يوسف (1898)

The cave dwellers of southern Tunisia; recollections of a sojourn with the Khalifa of Matmata - Bruun, Daniel (W. Thacker & Co, 1898)
p. 95 : Books written in the Berber langage are not to be found here ; so flir as we know (manuscripts have been discovered on the island of Jerba), the Berber dialect being written in Arabic characters. p. 305: Like their brethren in France, the Berber traders are born democrats.
Keywords: Récits de voyage – Djerba

Banani: the transition from slavery to freedom in Zanzibar and Pemba - Newman, Henry Stanley (Headley Brothers, 1898)
Keywords: Esclavage – Zanzibar

Le Djebel Nefousa. Transcription, traduction française et notes avec une étude grammaticale - Calassanti Motylinski, Adolphe de (Leroux, 1898)
Composed by Brahim ben Sliman Chemmakhi, Ṭālib from Īfren, 16 Ramaḍān 1302/1885. In the notes references to Shammākhī’s Siyar.
Keywords: Linguistique – Djebel Nefousa

Grammaire complète de la langue Mzabite comparée dans ses parties essentielles aux dialectes kabyles et tamacheks - Gourliau, Ernest (A. Legendre, 1898)
Keywords: Linguistique – Mzab

Voyage chez les Beni-Mzab (Sud de la Province d'Alger): contribution à l'étude de la Faune entomologique du Sahara algérien - Chobaut, Alfred (1898)
Keywords: Entomologie – Mzab